The Relationship between Self-Management and Quality of Life of Hypertension Patients at Grandmed Hospital, Lubuk Pakam - Simarmata, Pratiwi Christa; Wati, Syatria; Damayanti, Ade; Ahmad, Erwan; Khusna, Lailya; Octara, Debi Dhina (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Introduction: Hypertension is a chronic disease often referred to as a “silent killer” because it may progress without noticeable symptoms but can lead to serious complications such as stroke, heart failure, and kidney failure. Self-management plays an essential role in helping patients control blood pressure, adhere to medication therapy, and maintain an optimal quality of life. Methods: This study aims to determine the relationship between self-management and the quality of life of patients with hypertension at Grandmed Hospital Lubuk Pakam in 2025. Method: This study used a cross-sectional design with a total sample of 64 hypertensive patients selected using purposive sampling. Data were collected using a Self-Management questionnaire (40 items) and the WHOQOL-BREF to assess quality of life. Data were analyzed using the Chi-Square test with a significance level of 0.05. Results: The results showed that most respondents had good self-management (62.5%) and a good quality of life (92.2%). The Chi-Square test revealed a p-value of 0.041, indicating a significant relationship between self-management and the quality of life of hypertensive patients. Patients with good self-management demonstrated better physical, psychological, social, and environmental functioning compared to those with moderate self-management. Conclusion: Self-management has a significant relationship with the quality of life of hypertensive patients. Improving self-management behaviors such as medication adherence, low-salt diet, stress control, and regular physical activity contributes to a better quality of life. Continuous education and support from healthcare professionals are essential to help patients manage hypertension optimally.